Answer:
A quadratic equation
....[1] where, a, b and c are coefficient then;
the solution fore this equation we have;
....[2]
Given the function in the standard form:
![f(x) = -2x^2+x+5](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-2x%5E2%2Bx%2B5)
The quadratic equation is:
![0 = -2x^2+x+5](https://tex.z-dn.net/?f=0%20%3D%20-2x%5E2%2Bx%2B5)
On comparing with equation [1] we have;
a = -2 , b = 1 and c = 5.
The discriminant is given by:
![\text{Discriminant} = b^2-4ac](https://tex.z-dn.net/?f=%5Ctext%7BDiscriminant%7D%20%3D%20b%5E2-4ac)
then;
![\text{Discriminant} = (1)^2-4(-2)(5) = 1+40 = 41](https://tex.z-dn.net/?f=%5Ctext%7BDiscriminant%7D%20%3D%20%281%29%5E2-4%28-2%29%285%29%20%3D%201%2B40%20%3D%2041)
Solve for the zeros of the quadratic function:
Substitute the given values in [1] we have;
![x = \frac{-1 \pm \sqrt{41}}{2(-2)} = \frac{-1 \pm \sqrt{41}}{-4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-1%20%5Cpm%20%5Csqrt%7B41%7D%7D%7B2%28-2%29%7D%20%3D%20%5Cfrac%7B-1%20%5Cpm%20%5Csqrt%7B41%7D%7D%7B-4%7D)
then;
and ![x = \frac{-1 - \sqrt{41}}{-4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-1%20-%20%5Csqrt%7B41%7D%7D%7B-4%7D)
⇒
and ![x = \frac{1 + \sqrt{41}}{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B1%20%2B%20%5Csqrt%7B41%7D%7D%7B4%7D)
Therefore, the zeros of the given function are:
, ![\frac{1 + \sqrt{41}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%20%2B%20%5Csqrt%7B41%7D%7D%7B4%7D)